DETERMINISME IKLIM - Susfita, Oges; Syahibunnahar; Kustiawan; Calvin Antoni; Putri Febriyanti (Paradigma Mandiri : Jurnal Pengabdian Kepada Masyarakat, 2024)
This article discusses the theory of climate determinism and how it can be used to understand the development of society. This research focuses on analyzing the role of climate in shaping cultural, economic, and social characteristics in different regions of the world. Through case studies from different countries, this research shows how climate factors such as temperature, rainfall, and humidity have shaped settlement patterns, livelihoods, and social structures of communities. Findings from this study could contribute to a better understanding of the relationship between humans and their environment, as well as their implications for development and policy.